USING NEWS TO START CLASS: HOW SMALL DAILY INTERACTIONS AFFECT LARGER CLASSROOM INTERACTIONS - Dumin, Laura (Dialogue, 6(3), 2019)
In 2013, I added an extra credit assignment to my freshmen composition classes encouraging students to bring in news stories each class period; this assignment was designed to encourage students to be more willing to participate in classroom discussions. We then spent the first few minutes of each class discussing the stories they brought. After using this assignment for a few years, I had anecdotal evidence to suggest that my students were generally more talkative in class after the first week or two of sharing news. These experiences made me want to see if I could measure some change or document how students felt about discussing the news to start class. To that end, I developed a set of surveys to quantify this data. This article discusses the results of four semesters of survey and extra credit data from students bringing news stories to start their English classes. Keywords: student engagement, classroom management, teaching, freshman composition, SoTL, classroom discussions
Keywords: Type of access: Open Access